2019
DOI: 10.1088/1755-1315/331/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of digitalization on the performance of commercial banks in Nigeria

Abstract: This study investigates how digitalization enhances the performance of commercial banks adopting the purposive method and simple random sampling selecting 370 non-managerial employees from a commercial bank. A self-structured questionnaire was used as the major instrument for data collection and was analysed using SPSS version 25. From the result, it was discovered that there was a mild significant and positive relationship between the digitalization process and commercial bank performance (r = 0.114*; p<.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
1
11
0
1
Order By: Relevance
“…The research also reports that digitalization can increase productivity and decrease costs [5], thus leading to better performance. A study focusing on single countries, such as Nigeria, shows that digitalization, if adequately implemented, has a positive impact on the performance of commercial banks [6], whereas a study in China showed that investment in digitalization contributes to sustainable production improvements in commercial banks [7]. On the other hand, the research reports that digitalization does not come free of operational risks [8] and that the digitization of banking poses a threat to several areas, including security [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research also reports that digitalization can increase productivity and decrease costs [5], thus leading to better performance. A study focusing on single countries, such as Nigeria, shows that digitalization, if adequately implemented, has a positive impact on the performance of commercial banks [6], whereas a study in China showed that investment in digitalization contributes to sustainable production improvements in commercial banks [7]. On the other hand, the research reports that digitalization does not come free of operational risks [8] and that the digitization of banking poses a threat to several areas, including security [9].…”
Section: Introductionmentioning
confidence: 99%
“…Cont. Authors prepared the table based on the data available on the websites of the analyzed banks on 31 March 2021 [30-56,61], ABS[58], and the UN Global Compact[6].…”
mentioning
confidence: 99%
“…Similarly, a study by Selim et al [42] on teachers' acceptance of ICT integration in teaching deduced that skill inadequacy contributed to little confidence in using ICT technology, thus a significant influence in ICT implementation in universities in Malaysia. Further, Agboola et al [43] investigated the preparedness of university lecturers for the introduction of ICT in the International Islamic University of Malaysia established that confidence and training in ICT was a significant predictor of ICT implementation. us, the correlation implied that trained lecturers' exhibited substantial levels of preparedness and demonstrated confidence in integrating ICT.…”
Section: Ict Implementation Information Communication Technology (Ict...mentioning
confidence: 99%
“…Другое похожее исследование было проведено M. Agboola et al, в котором анализировалось влияние цифровизации на эффективность работы коммерческих банков в Нигерии [22]. В этом исследовании использован прямой статистический метод и выборка из 370 сотрудников коммерческих банков.…”
Section: теоретический обзорunclassified